Rapid Proteome Changes in Plasma and Cerebrospinal Fluid Following Bacterial Infection in Preterm Newborn Pigs - Muk, Tik; Stensballe, Allan; Pankratova, Stanislava; Nguyen, Duc Ninh; Brunse, Anders; Sangild, Per Torp; Jiang, Ping-Ping (Frontiers in Immunology, 2019)
Background: Neonatal infection and sepsis are common for preterm infants due to their immature immune system. Early diagnosis is important for effective treatment but few early markers of systemic and neuro-inflammatory responses in neonates are known. We hypothesized that systemic infection with Gram-positive Staphylococcus epidermidis (SE) induces acute changes to proteins in plasma and cerebrospinal fluid (CSF), potentially affecting the immature brain of preterm neonates. Methods: Using preterm pigs as model for preterm infants, plasma and CSF samples were collected up to 24 h after SE infection and investigated by untargeted mass spectrometry (MS)-based proteomics. Selected differential proteins were further studied in vitro assays. Results: The clinical signs of sepsis and neuroinflammation in SE-infected piglets were associated with changes in multiple CSF and plasma proteins. Eight plasma proteins, including APOA4, haptoglobin, MBL1, vWF, LBP and sCD14, were affected already 6 h after infection. Likewise, acute phase reactants, including complement components, showed a time-dependent activation pattern after infection. Feeding bovine colostrum reduced the sepsis-related change in clinical parameters as well as plasma proteins. Neuroinflammation-related neuropeptide Y (NPY), IL-18 and MMP-14 showed distinct changes in the CSF and several brain regions (prefrontal cortex, PVWM, hippocampus) 24 h after infection. These changes were verified in TLR2 agonist-challenged primary microglia cells, where exogenous NPY suppressed the inflammatory response. Conclusion: Systemic infection with Gram-positive SE induces inflammation with rapid proteome changes in plasma and CSF in preterm newborn pigs. The observed early markers of sepsis and neuroinflammation in preterm pigs may serve as novel biomarkers for sepsis in preterm infants.